2000
DOI: 10.1093/oxfordjournals.aje.a010145
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Transmissible Diseases after Elimination

Abstract: Elimination of an infectious disease is often understood to mean the total absence of cases in a population. This situation can occur only if the entire population is immune as a result of either natural disease or vaccination. However, this costly and unrealistic scenario is not necessary to ensure elimination, more appropriately defined as a situation in which sustained transmission cannot occur and secondary spread from importations of disease will end naturally, without intervention. The authors describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
183
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 0 publications
4
183
1
4
Order By: Relevance
“…20 High vaccination coverage of pre-school children for two MMR doses must continue in order to achieve measles elimination in Australia. 1,2,6 This study indicates that strategies to help achieve this need to address parent and provider knowledge about the MMR vaccination schedule and about medical contraindications to vaccination. Improved reporting of MMR2 vaccinations to the ACIR is essential for more accurate measurement of MMR coverage and thus better monitoring of Australia's progress towards measles elimination.…”
Section: Discussionmentioning
confidence: 98%
“…20 High vaccination coverage of pre-school children for two MMR doses must continue in order to achieve measles elimination in Australia. 1,2,6 This study indicates that strategies to help achieve this need to address parent and provider knowledge about the MMR vaccination schedule and about medical contraindications to vaccination. Improved reporting of MMR2 vaccinations to the ACIR is essential for more accurate measurement of MMR coverage and thus better monitoring of Australia's progress towards measles elimination.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, it is not safe to conclude that epidemiological patterns seen in the immediate aftermath of eradication will continue to hold. For instance, as population immunity against orthopoxvirus infection declines, the fraction of monkeypox cases owing to secondary transmission is expected to rise because human-to-human transmission becomes more efficient [53].…”
Section: Implications For Eradication Programmesmentioning
confidence: 99%
“…There are many methods to estimate R e when appropriate data is available on epidemic curves and outbreak size, duration, distribution etc. [13][14][15] Vaccine efficacy depends on the age of vaccination and other epidemiological contexts. Some studies have shown that the efficacy of measles vaccine administered at 9-11 months of age is of the order of 85-90% in the Indian context.…”
Section: Introductionmentioning
confidence: 99%